Determinants of winegrowers' profitability: evidence from an Eastern Europe wine region. Issue 3 (4th September 2017) - De Salvo, Maria; Begalli, Diego; Capitello, Roberta; Agnoli, Lara; Tabouratzi, Efthalia
Abstract : Purpose: The purpose of this paper is to identify the main determinants of winegrowers' profitability in Eastern Europe with the ultimate purpose to improve the wine industry competitiveness. Design/methodology/approach: The research is focussed on the Moldova region (Romania), a little studied wine-growing area that presents potential for the future development of the wine industry. A hierarchical approach is applied to consider the simultaneous effects of climate aspects, vineyard features, winegrowers' characteristics and management practices on vineyards' profitability. The model is based on data from 274 vineyards managed by 64 winegrowers, where 32 different grape varieties are cultivated in different districts. Different scenarios are simulated and alternative policies are analysed. Findings: Climate aspects and human factors, particularly the educational level and type of agriculture practiced, emerge as main determinants. Farmers' climate change perceptions also have a primary role. The grape variety affects profitability differences across vineyards at a lower extent. Research limitations/implications: The study suggests an approach easily replicable to other viticultural contexts. Practical implications: Results are useful for policymakers in order to forecast the impact of policies devoted to improving the wine industry competitiveness in Eastern Europe. Originality/value: The study presents a micro-scale analysis in which the effects of climate aspects, vineyard features, winegrowers' characteristics and management practices are simultaneously estimated. It also produces new knowledge in a little studied wine region.